Fluorescence Imaging Using Enzyme-Activatable Probes for Real-Time Identification of Pancreatic Cancer - Takahashi, Ryugen; Ishizawa, Takeaki; Sato, Masumitsu; Inagaki, Yoshinori; Takanka, Mariko; Kuriki, Yugo; Kamiya, Mako; Ushiku, Tetsuo; Urano, Yasuteru; Hasegawa, Kiyoshi (Frontiers in Oncology, 2021)
Introduction Radical resection is the only curative treatment for pancreatic cancer, which is a life-threatening disease. However, it is often not easy to accurately identify the extent of the tumor before and during surgery. Here we describe the development of a novel method to detect pancreatic tumors using a tumor-specific enzyme-activatable fluorescence probe. Methods Tumor and non-tumor lysate or small specimen collected from the resected specimen were selected to serve as the most appropriate fluorescence probe to distinguish cancer tissues from noncancerous tissues. The selected probe was sprayed onto the cut surface of the resected specimen of cancer tissue to acquire a fluorescence image. Next, we evaluated the ability of the probe to detect the tumor and calculated the tumor-to-background ratio (TBR) by comparing the fluorescence image with the pathological extent of the tumor. Finally, we searched for a tumor-specific enzyme that optimally activates the selected probe. Results Using a library comprising 309 unique fluorescence probes, we selected GP-HMRG as the most appropriate activatable fluorescence probe. We obtained eight fluorescence images of resected specimens, among which four approximated the pathological findings of the tumor, which achieved the highest TBR. Finally, dipeptidyl-peptidase IV (DPP-IV) or a DPP-IV-like enzyme was identified as the target enzyme. Conclusion This novel method may enable rapid and real-time visualization of pancreatic cancer through the enzymatic activities of cancer tissues.